2015
DOI: 10.1007/s10728-015-0301-3
|View full text |Cite
|
Sign up to set email alerts
|

Speaking Out and Being Heard Residents’ Committees in Quebec’s Residential Long-Term Care Centre

Abstract: Residents' councils in Quebec's residential and long-term care centres have the mandate to promote the improvement of living conditions for residents, to assess their level of satisfaction, and to defend their rights. Based on two studies on the autonomy of councils, we examined how committees can express themselves on topics other than those the management is already aware of, to reveal various previously unknown aspects of the services, and to voice unexpressed concerns. We are especially interested in what … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Like all healthcare organizations, LTC facilities in Québec have been operating on tight budgets and limited staff for the past two decades. Gagnon et al (2017) reported staff shortages, high turnover of staff and reliance on private staffing agencies as problematic issues in delivering multidisciplinary care in LTC. This challenging organizational setting has meant physicians, nurses, and orderlies often face difficult situations.…”
Section: Pre-covid-19 Contextmentioning
confidence: 99%
“…Like all healthcare organizations, LTC facilities in Québec have been operating on tight budgets and limited staff for the past two decades. Gagnon et al (2017) reported staff shortages, high turnover of staff and reliance on private staffing agencies as problematic issues in delivering multidisciplinary care in LTC. This challenging organizational setting has meant physicians, nurses, and orderlies often face difficult situations.…”
Section: Pre-covid-19 Contextmentioning
confidence: 99%